Arab spring dreams the next generation speaks out for freedom and justice from North Africa to Iran - Ahmari, Sohrab; Weddady, Nasser; Steinem, Gloria
"During the Arab Spring, the world saw a long-suppressed group in the Middle East--young people--assert itself and demand its rights. But youthful dissent did not appear overnight; for decades it has been simmering beneath the surface in countries from Saudi Arabia to Yemen, from Iran to Egypt. In Arab Spring Dreams, a number of young Middle Easterners describe their experiences with the region's laws and cultural mores, including the crime of holding hands before marriage, discrimination and harassment over religious beliefs, and young women fighting for the right to complete their educations. They also discuss how previous uprisings, particularly the American civil rights movement of the 1960s, might be channeled to effect change in their own countries. Beautifully written and profoundly moving, these stories present a decisive call for change at a crucial point in the evolution of the Middle East"-- Provided by publisher.